Tracking spending on malaria by source in 106 countries, 2000-16: an economic modelling study - Haakenstad, Annie; Harle, Anton Connor; Tsakalos, Golsum; Micah, Angela E; Tao, Tianchan; Anjomshoa, Mina; Cohen, Jessica; Fullman, Nancy; Hay, Simon I; Mestrovic, Tomislav; Mohammed, Shafiu; Mousavi, Seyyed Meysam; et al. (The lancet. Infectious diseases, 2019)
Background: Sustaining achievements in malaria control and making progress toward malaria elimination requires coordinated funding. We estimated domestic malaria spending by source in 106 countries that were malaria-endemic in 2000-16 or became malaria-free after 2000. Methods: We collected 36 038 datapoints reporting government, out-of-pocket (OOP), and prepaid private malaria spending, as well as malaria treatment-seeking, costs of patient care, and drug prices. We estimated government spending on patient care for malaria, which was added to government spending by national malaria control programmes. For OOP malaria spending, we used data reported in National Health Accounts and estimated OOP spending on treatment. Spatiotemporal Gaussian process regression was used to ensure estimates were complete and comparable across time and to generate uncertainty. Findings: In 2016, US$4·3 billion (95% uncertainty interval [UI] 4·2-4·4) was spent on malaria worldwide, an 8·5% (95% UI 8·1-8·9) per year increase over spending in 2000. Since 2000, OOP spending increased 3·8% (3·3-4·2) per year, amounting to $556 million (487-634) or 13·0% (11·6-14·5) of all malaria spending in 2016. Governments spent $1·2 billion (1·1-1·3) or 28·2% (27·1-29·3) of all malaria spending in 2016, increasing 4·0% annually since 2000. The source of malaria spending varied depending on whether countries were in the malaria control or elimination stage. Interpretation: Tracking global malaria spending provides insight into how far the world is from reaching the malaria funding target of $6·6 billion annually by 2020. Because most countries with a high burden of malaria are low income or lower-middle income, mobilising additional government resources for malaria might be challenging. Funding: The Bill & Melinda Gates Foundation.
Gesehen am 21.08.2019